LOW TEMPERATURE TOLERANCE OF VARIETIES OF THE UNABI PLANT (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The scientific paper conducted research on the organization and cultivation of unab plantations in the conditions of the Kashkadarya oasis. During the experiments, 5 varieties of unabi, such as ta-yan-sizo, u-sin-hun, and the recently introduced varieties of mayabaizao, jixinzao, and zanhuangdazao from China, were found to be resistant to dry low temperatures. The degree of damage to the vegetative organs of plants aged 2-3 and 1-8 years at low temperatures was analyzed.